Are marginal bone level changes around dental implants due to infection?. (18th January 2021) - Coli, Pierluigi; Jemt, Torsten
Abstract: Background: Peri‐implant bone level values have been used as the clinical standard of reference to describe the status of a dental implant. Reduction of marginal bone levels in association with bleeding on probing have been claimed to be a sign of pathology and an indication of treatment needs. Purpose: To assess the available evidence that peri‐implant bone loss is caused by infection. Materials and methods: This article is a narrative review on the interpretation of marginal bone level changes around dental implants as a consequence of infection. Results and conclusions: There is evidence that plaque accumulation induces an inflammatory reaction in the peri‐implant soft tissues and that resumption of plaque control measures results in the reduction of the inflammation. Since plaque is always present in the oral cavity, a cause‐effect relationship between plaque accumulation and peri‐implantitis, defined as inflammation of the peri‐implant soft tissues associated with marginal bone loss has been difficult to validate and has not been proven so far. There is no evidence of the mechanisms involved in the tissue reactions resulting in the conversion from a state of an inevitable inflammation contained in the soft tissues to a state of inflammation involving the loss of peri‐implant marginal bone. There is today no consensus whether implants should be expected to be surrounded by tissues which are completely free from inflammation, or that an "immune‐driven", chronic, subclinical inflammation should be expected at the foreign body implant. The infectious origin theory appears to be mainly supported by ligature‐induced experimental peri‐implantitis investigations in animal models that suffer of several methodological problems, and therefore, provide misleading information with regards to human clinical applications in large, routine populations.